Reading the news online: Effects of medium on knowledge acquisition. - Omar, Bahiyah (2008)
The Internet has exerted its influence in the presentation and consumption of news. With many desirable characteristics, the Internet has become a powerful news medium. Nevertheless, studies claim that the online news medium is less effective than print for the learning of news facts. Studies measuring knowledge acquisition usually examine the ability to recall facts - factual knowledge - and often ignore the ability to connect information - structural knowledge – though the latter facilitates the process of decision making and problem solving. Employing an experimental method, this study found no evidence to support the claim that the traditional print newspaper is superior to online media in fostering factual knowledge. The study equally found no support for the prediction that the online medium – whose structure resembles the associative nature of human memory - is superior to print in fostering structural knowledge. The lack of support for these hypotheses has methodological implications and invites further investigations.